2023
DOI: 10.1007/s11255-023-03578-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the levels of anxiety and depression among patients with end-stage renal disease undergoing hemodialysis

Abstract: Back ground Hemodialysis (HD) is a lifesaving procedure required for many patients with end stage renal disease (ESRD) who are not able to undergo a kidney transplant. However, HD could cause anxiety and depression for those patients. This study aimed to assess the levels of anxiety and depressive symptoms and find out the predictors affecting them. Materials and methods A cross-sectional, descriptive correlational design was adopted on a sample of 230 patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…This could be because of the damage that long-term high blood pressure does to the kidneys' blood vessels and filtering systems. These findings are consistent with previous research (Eckardt et al, 2023;Kaneyama et al, 2023;Qawaqzeh et al, 2023;Sawhney et al, 2023) that has demonstrated the association between hypertension and renal dysfunction in individuals with type 2 diabetes. Regarding laboratory parameters, patients with hypertension had significantly higher total cholesterol levels compared to those without hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This could be because of the damage that long-term high blood pressure does to the kidneys' blood vessels and filtering systems. These findings are consistent with previous research (Eckardt et al, 2023;Kaneyama et al, 2023;Qawaqzeh et al, 2023;Sawhney et al, 2023) that has demonstrated the association between hypertension and renal dysfunction in individuals with type 2 diabetes. Regarding laboratory parameters, patients with hypertension had significantly higher total cholesterol levels compared to those without hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This illustrates the uneven distribution of respondents, so the results do not fit with the theory that education level can affect anxiety levels. Another factor in reducing anxiety as a trait was education (Qawaqzeh et al, 2023). The result is consistent with previous studies, which also found no correlation between respondents' education and anxiety levels.…”
Section: Relationship Between Educational Level and Anxiety Levelsupporting
confidence: 90%
“…Compared to other chronic diseases like diabetes or congestive heart failure, their incidence is significantly higher. In addition to depression, patients also suffered from anxiety with about 50% of patients showing increased levels of anxiety (Qawaqzeh et al, 2023). People with chronic renal disease who are receiving hemodialysis experience anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinicians neglect the psychological problems of depression and anxiety among dialysis patients, particularly those in the final stages of their disease (Qawaqzeh et al, 2023). A deeper understanding of the prevalence of these disorders, as well as the factors that contribute to the severity of these diseases in hemodialysis patients, is required.…”
mentioning
confidence: 99%